Dung beetle community dynamics in undisturbed tropical forests: implications for ecological evaluations of land‐use change. Issue 1 (12th November 2016) - Beiroz, Wallace; Slade, Eleanor M.; Barlow, Jos; Silveira, Juliana M.; Louzada, Julio; Sayer, Emma
Abstract: The impacts of human activities on tropical forests are widespread and increasing. Hence, a good knowledge base about ecological processes in undisturbed tropical forest is crucial to provide a baseline for evaluating anthropogenic change. Our 5‐year study focused on understanding the background spatial and inter‐annual variation in dung beetle communities at 12 sites of undisturbed lowland tropical rainforest in the Brazilian Amazon. We then assessed how this variation may affect ecological evaluations of anthropogenic influence by comparing community metrics with comparable dung beetle data collected from 15 sites of Eucalyptus plantation in the same region. Of all measured environmental variables, soil texture best explained spatial variation in dung beetle communities in undisturbed forests. Furthermore, soil texture was important for community assembly as it was associated with dung beetle nesting behaviours. While the relative abundance of dung beetle functional groups was stable over time, there were important inter‐annual temporal dynamics, with a fivefold variation in abundance and body mass, and with species richness ranging from 52 to 74. These temporal oscillations were probably caused by variation in dry season rainfall. This inter‐annual variation influenced the comparison between undisturbed forests and plantations, which could lead to inconsistencies in evaluation of anthropogenic change. We therefore highlight the importance of understanding natural variation in studies evaluating the consequences of land‐use change and other forest disturbances on forest biodiversity.